2006
DOI: 10.1176/ps.2006.57.4.531
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Missed First Appointments at Community Mental Health Centers After Psychiatric Hospitalization

Abstract: Clinical, policy, and programmatic implications may be elaborated by studying risk factors for nonadherence in a community mental health setting. Given the multitude of problems associated with nonadherence, interventions should be tailored around specific characteristics that elevate the risk of nonadherence, especially nonadherence in the form of failure to attend the first appointment after psychiatric hospitalization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
48
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(54 citation statements)
references
References 18 publications
5
48
1
Order By: Relevance
“…This analysis was part of a study aimed at determining predictors of non-adherence with the first scheduled community mental health outpatient appointment following hospitalization [17]. Inclusion in the study was restricted to consecutively discharged patients with a scheduled follow-up appointment at any of 12 participating community mental health settings in a single urban county.…”
Section: Methodsmentioning
confidence: 99%
“…This analysis was part of a study aimed at determining predictors of non-adherence with the first scheduled community mental health outpatient appointment following hospitalization [17]. Inclusion in the study was restricted to consecutively discharged patients with a scheduled follow-up appointment at any of 12 participating community mental health settings in a single urban county.…”
Section: Methodsmentioning
confidence: 99%
“…A study of the management of 3923 patients with diabetes in primary care found that those with secure attachment styles (as assessed by the Relationship Questionnaire) were significantly more likely to attend than those with dismissing attachment styles (Ciechanowski et al, 2006). Compton et al (2006) collected data from team members and medical notes on 234 consecutively discharged patients from two in-patient units in a US urban county hospital. In a logistic regression model, the four characteristics that were significant predictors of missed first appointments were involuntary legal status at discharge or leaving against medical advice, not having an established out-patient clinician, an Axis IV problem relating to the patient's primary support group (for example, death of a family member or health problems in the family) and the number of days from discharge to the follow-up appointment.…”
Section: Why Don't Patients Attend Their Appointments?mentioning
confidence: 99%
“…Consecutive discharges from each of these two units were studied as part of a project to examine predictors of outpatient nonadherence (9). Due to the inclusion criteria of the parent study, charts of patients discharged with follow-up appointments to clinics other than the designated clinics in the metropolitan county in which the hospital is located (e.g., to private practices or to community mental health centers in other counties) were excluded.…”
Section: Setting and Samplementioning
confidence: 99%
“…This analysis was conducted using data from a study that examined predictors of nonadherence with the first outpatient community mental health follow-up appointment after psychiatric hospitalization (9). The aim of this analysis was to investigate the predictors of LOS on two inpatient psychiatric units in a large, urban, university-affiliated, county hospital.…”
Section: Introductionmentioning
confidence: 99%